Performance and characterizations of EMIMTf2N and silica direct blending in mixed matrix membrane for CO2/CH4 separation - Alwani Shafie, S.N. (Amirkabir University of Technology - Membrane Processes Research Laboratory, 2020)
Ionic liquids (ILs) have been studied for CO2 capture owing to the excellent properties of having high CO2 affinity and negligible vapor pressure. The incorporation of IL in polycarbonate (PC) based Mixed Matrix Membrane (MMM) is becoming one of the promising approaches for developing membrane for CO2/CH4 separation. Silica nanoparticle has also been proven to improve performance of MMM for CO2/CH4 separation. Thus, this study investigates the effect of direct blending of IL (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, EMIMTf2N) and silica into the MMM on its properties and CO2/CH4 separation performances. The immobilization of silica particles and EMIMTf2N was confirmed from the FTIR peaks data. The IL in the MMM significantly increases the MMM rigidity as ascribed by its enhanced glass transition temperature. The IL in the MMM improves the interaction by acting as a bridging agent between silica particles and PC. The MMM with 1 wt% of fillers and IL shows the highest performance by enhancing CO2 permeability by 13 folds and selectivity by 35% compared to that of pure PC membrane. The results suggest that low loading of silica/IL in MMM is noteworthy to be explored and further studies at high loading are warranted. Â© 2020 MPRL. All rights reserved.